Counselor Trainee Cognitive Complexity: Peer Interactions and Assessments - Alexandra Gantt-Howrey; Erin Woods; Gulsah Kemer (Teaching and Supervision in Counseling, 2024)
In their training efforts, counselor educators focus on a variety of characteristics, including cognitive complexity (CC). Cognitively complex counselors can identify and integrate the multiple characteristics and perspectives of their clients and have been found to be generally more empathic and accepting of ambiguity (Castillo 2018; Granello, 2010; Welfare & Borders, 2010b). Although CC is considered as an integral counselor attribute (Castillo, 2018), how CC may be related to within-program peer interactions has yet to be explored. Through this convergent mixed methods study (Creswell & Creswell, 2017), we sought to understand how n = 7 participants’ experiences with and assessments of their counseling peers may help explain the quantitative differences between participants’ levels of CC, using the Counselor Cognitions Questionnaire (Welfare & Borders, 2010b). Qualitative findings reveal that counselors in training assess their peers according to their professional abilities, developmental tasks, and perceived similarities and differences with them. Level of CC was found to be positively associated with perceptions related to peers’ developmental levels.
Keywords: cognitive complexity; counselor development; counselor training